Non-Measuring Camera Monitoring of Comprehensive Displacement of Simulated Slope Mass Based on Edge Extraction of Subpixel Ring Mark - Yu Han; Xugang Lian; Fan Wang; Haodi Fan (Applied Sciences, 2022)
Slope hazards threaten the safety of buildings and people’s lives and property. Real-time and dynamic monitoring of slope deformation by digital image monitoring technology is an effective method to prevent slope hazards. In this study, the Zhang Zhengyou calibration method is used to calibrate a non-metric digital camera, which is used to monitor the simulated slope with ring marks. The sub-pixel algorithm is used to identify the center coordinates of the landmarks. The proportional coefficient is obtained from the relationship between the landmarks and the actual distance. The change in displacement of the position of the digital camera is calculated in combination with the specific displacement value of the slope, yielding the rapid and accurate displacement trend of the slope. The outdoor experimental results show that the monitoring accuracy of this method can reach millimeter level, which can meet the demand of slope monitoring.